Media pembelajaran Snack Up! Eduventure (Ular Tangga Jumbo) - Syahariya, Aura Anya (Maliki Interdisciplinary Journal, 2025)
Education aims to optimize the potential of students through an environment and learning process that supports spiritual development, self-control, personality, intelligence, character, and essential skills. Educators play a central role as facilitators who create meaningful and relevant learning experiences. Conventional lecture-centered learning tends to be less effective in maintaining student attention and participation. Therefore, innovative learning media are essential to stimulate motivation, enhance interaction, and create a enjoyable learning atmosphere. One intriguing innovation is the use of game-based learning media, such as Jumbo Snakes and Ladders. This medium adapts the traditional snakes and ladders game into a large-scale format suitable for group play, integrating subject-related questions or challenges into each square. The objective of this study is to develop effective, engaging, and interactive learning with educators serving as facilitators.